Dear teachers, Do you know? The era of teaching is over, only learning prevails - Kumar Shah, Rajendra; Basnyat, Samjhana (Edelweiss Applied Science and Technology, 2024)
Traditional teacher-centered teaching causes significant difficulties for both teachers and students. In this model, the teacher is active, delivering knowledge, while the student remains passive, attempting to absorb it. This approach often results in frustration for students as they struggle to memorize the teacher's words without truly understanding the subject matters. Traditional teaching methods not only cause suffering and pain for both teachers and students, but they also stifle students' creativity. These methods promote rote memorization of the teacher's words. Therefore, it is urgent to replace traditional teaching with more effective learner centred approaches. The main objective of this study is to analyze the pain, suffering, and challenges I faced with traditional teaching methods and how these experiences prompted changes in my pedagogy. I used multiple paradigms, and autoethnography as a strategy of inquiry, which combines personal experience and writing. I selected three participants based on their availability and willingness to be interviewed: a former colleague who teaches social studies and two of my former social studies students. In this study, I present my teaching experiences at the school level in the first section and at the university level in the second section. Initially, while teaching at the school level, I adopted traditional teacher centred teaching methods. Gradually, I recognized the weaknesses in these methods. Despite this realization, my teaching approach remained teacher-centered during my time at the school level. When I began teaching at the university level, I realized the need to improve my pedagogical practices. Consequently, I adapted my pedagogical practices to meet the needs of the students. This student-centered teaching method enabled the development of the knowledge, skills, and competencies I aimed to cultivate in them.